2015
DOI: 10.1002/jib.252
|View full text |Cite
|
Sign up to set email alerts
|

Impact odorants and sensory profile of young red wines from four Galician (NW of Spain) traditional cultivars

Abstract: Monovarietal red wines from Caíño da Terra, Caíño Longo, Caíño Bravo and Caíño Redondo grape varieties were analysed in order to determine the volatile composition in terms of fermentative compounds. The wines were also sensorially evaluated with the aim of defining their sensory profile based on the descriptive attributes provided by a panel. Significant analytical and sensorial differences were found among the four wine cultivars. The wine from the Caíño Redondo cultivar showed a lower content for the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
0
11
0
9
Order By: Relevance
“…The concentration of ethyl lactate in wines elaborated from untreated grapes was the highest. This compound appears generally in relatively high amounts when lactic acid has formed in malolactic fermentation (Cortés-Diéguez et al, 2015). The wine concentration of diethyl succinate in Ur and Ur+S samples was lower than control and Arg wines.…”
Section: Effects Of Foliar N Applications To 'Cabernet Sauvignon' Gramentioning
confidence: 90%
See 1 more Smart Citation
“…The concentration of ethyl lactate in wines elaborated from untreated grapes was the highest. This compound appears generally in relatively high amounts when lactic acid has formed in malolactic fermentation (Cortés-Diéguez et al, 2015). The wine concentration of diethyl succinate in Ur and Ur+S samples was lower than control and Arg wines.…”
Section: Effects Of Foliar N Applications To 'Cabernet Sauvignon' Gramentioning
confidence: 90%
“…The wine concentration of diethyl succinate in Ur and Ur+S samples was lower than control and Arg wines. Diethyl succinate increases after the aging of the wine; however, its composition is representative of the wine distillate (Cortés-Diéguez et al, 2015). Ethyl lactate and diethyl succinate did not contribute to the Cabernet Sauvignon wine aroma (OAVs < 0.2) ( Table 3).…”
Section: Effects Of Foliar N Applications To 'Cabernet Sauvignon' Gramentioning
confidence: 95%
“…The use of B. bruxellensis as a pure brewing strain, generally, lead to beers containing a large variety of esters, such as ethyl acetate, ethyl lactate, ethyl caproate, and ethyl caprylate. These compounds are desirable; if present in moderate levels, they help increase the flavor complexity of beers, whereas high amounts affect negatively beverage aroma, conferring undesirable, solvent-like buttery and medicinal notes [30]. Otherwise, most authors reported very low quantities of isoamyl acetate, which could be explained by the ability of B. bruxellensis to break down this aroma compound, which is highly desirable in wheat beer [31].…”
Section: Non-conventional Yeasts For Bioflavoringmentioning
confidence: 99%
“…De entre los compuestos aromáticos volátiles para todos los vinos, los OAV más altos fueron exhibidos por el octanoato de etilo (aroma frutal, manzana) y acetato de isoamilo (aroma de plátano), ambos en el vino elaborado con la cepa Mp278 (OAV = 58.00 y 55.72, respectivamente). En cuanto a los alcoholes superiores, los vinos elaborados con la cepa Sb474 produjeron la mayor concentración del compuesto propanol (64 mg/L; OAV = 77.11), con efectos sinérgicos que refuerzan el aroma afrutado a concentraciones comprendidas en el intervalo 11-68 mg/L (Conde González et al, 2010; Cortés-Diéguez et al, 2015).…”
Section: Caracterización Aromática De Los Vinosunclassified
“…Los alcoholes evolucionan poco en el tiempo, aunque pueden aumentar débilmente debido a la hidrólisis de sus acetatos (Dubois, 1994). Los compuestos 1propanol, isobutanol (2-metil-propanol) y 3-metil-butanol fueron los alcoholes superiores más abundantes y se consideran muy importantes en el aroma del vino (Cortés-Diéguez et al, 2015).…”
Section: Caracterización Aromática De Los Vinosunclassified